Spatio-Temporal Patterns of Climatic Niche Dynamics of an Invasive Plant Mikania micrantha Kunth and Its Potential Distribution Under Projected Climate Change - Banerjee, Achyut Kumar; Mukherjee, Abhishek; Guo, Wuxia; Liu, Ying; Huang, Yelin (Frontiers in Ecology and Evolution, 2019)
Similarity of climatic niches occupied by a species in its native and invasive ranges has been recognized as one of the key factors for successful invasion. Accounting for changes in climatic niche over time may provide better understanding of the dynamic biological invasion process. We investigated these changes for an invasive alien plant Mikania micrantha in South and Southeast Asia, Australia, Oceania and parts of the USA. Based on documented occurrences over 200 years (1800-2017), we reconstructed the introduction history of the species and estimated climatic niche dynamics for the presumed invasion routes. We estimated niche conservatism and the environmental analogy between native and invasive ranges and used ecological niche modelling to identify the potential distribution of M. micrantha under current and future climate change scenarios. Our study identified six pathways through which the species was presumably introduced from its native range. Climatic conditions of the initial introduction sites were found to be similar to those in the native niche. However, the species occupied climatic niches in dry and cold areas over time, being outside of the limits of the realized climatic niche of its native range. The climatic niche dynamics also differed between the invasion pathways with variable time lag. This pattern of niche change over time was found to be consistent in future. Nearly 20% of the invasive range was found to be climatically suitable for this species and was predicted to expand towards cold and dry areas of the invasive range affecting nearly half of the global biodiversity hotspots. By analyzing M. micrantha invasion at a time scale, this study revealed multiple introduction pathways, variation in climatic niche dynamics among invasion routes, and potential range expansion of the species in its invasive range. Although further experimental and molecular studies are needed to explain these findings fully, this study highlights the need for temporally explicit approaches towards better understanding and successful management of biological invasions.